Rancang Bangun Alat Tanam Benih Kangkung Darat (Ipomoea Raptana Poir) - Nasichin Nasichin; Fajarsukoco Fajarsukoco; Duta Satria; Yose Sebastian; Meinilwita Yulia (Jurusan Teknologi Pertanian, 2020)
Kale spinach is a type of vegetable that is widely consumed by people in Indonesia. It’s contains protein, carbohydrates, calcium, iron, sodium, phosphorus, fiber, vitamins A and C. The kale spinach is a low-calorie vegetable. The purpose of this research is to design kale spinach seed planting tool with a semi-mechanical system which power comes from human power, this tool is operated by pulling a lever on the tool so that the tool can work. After the manufacture of kale seed planting is complete, the authors test the performance of the tool capacity, and from the results of the performance test of this tool it can be concluded that it can work well. The results of the performance test of the capacity of this tool to plant water spinach seeds with an area of 0.0005 ha takes 0.007 hours with an average speed of 0.2 m/s, the average seeds that fall per hole are 3 seeds, 98.6% efficiency, The theoretical capacity is 0.072 ha/hour, the effective capacity is 0.071 ha/hour, the percentage of growth is 95%, the average distance between plants is 10 cm, and the average distance between rows of plants is 10 cm.